Mindfulness‐based cognitive therapy for prevention and time to depressive relapse: Systematic review and network meta‐analysis. (27th October 2020) - McCartney, Mark; Nevitt, Sarah; Lloyd, Annette; Hill, Ruaraidh; White, Ross; Duarte, Rui
Abstract: Objective: To perform a network meta‐analysis (NMA) to compare the long‐term effectiveness of mindfulness‐based cognitive therapy (MBCT) with available strategies for prevention and time to depressive relapse. Methods: Seven electronic databases were searched up to June 2019. Studies evaluated MBCT for the management of depression‐related outcomes and follow‐up assessments occurred at 12 months or longer. Results: Twenty‐three publications were included, 17 of which were randomised controlled trials (RCTs). Data from 14 RCTs including 2077 participants contributed to meta‐analysis (MA) and NMA to assess relapse of depression and 13 RCTs with 2017 participants contributed to MA and NMA for time to relapse of depression. NMAs showed statistically significant advantages for MBCT over treatment as usual (TAU) for relapse of depression (RR = 0.73, 95% CI 0.54 to 0.98) and for MBCT over TAU and placebo for time to relapse of depression (MBCT vs TAU: HR = 0.57, 95% CI 0.37 to 0.88; MBCT vs placebo: HR = 0.23, 95% CI 0.08 to 0.67). Subgroup meta‐analysis of relapse of depression by previous number of depressive episodes showed similar results between subgroups. Subgroup meta‐analysis by the use or not of booster sessions suggests these may lead to improved effectiveness. Conclusions: MBCT is more effective than TAU in the long‐term in preventing relapse of depression and has statistically significant advantages over TAU and placebo for time to relapse of depression. No statistically significant differences were observed between MBCT and active treatment strategies for rate of relapse or time to relapse of depression.